2006
DOI: 10.1056/nejmoa055706
|View full text |Cite
|
Sign up to set email alerts
|

Intracoronary Injection of Mononuclear Bone Marrow Cells in Acute Myocardial Infarction

Abstract: With the methods used, we found no effects of intracoronary injection of autologous mononuclear BMC on global left ventricular function.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
739
5
17

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 1,166 publications
(775 citation statements)
references
References 40 publications
8
739
5
17
Order By: Relevance
“…The average baseline ejection fraction was about 55% by contrast ventriculography, about 54% by echocardiography, and about 47% by MRI. In the trial conducted by Lunde et al, 6 there was no significant improvement in LVEF at 6 months in the mononuclear BMC group as compared to the control group. It may be worth mentioning that the number of stem cells administered to the patients was less than in the other studies and this may contribute to the lack of effectiveness in this study.…”
Section: Lvef Change Noted In Individual Studiesmentioning
confidence: 84%
See 4 more Smart Citations
“…The average baseline ejection fraction was about 55% by contrast ventriculography, about 54% by echocardiography, and about 47% by MRI. In the trial conducted by Lunde et al, 6 there was no significant improvement in LVEF at 6 months in the mononuclear BMC group as compared to the control group. It may be worth mentioning that the number of stem cells administered to the patients was less than in the other studies and this may contribute to the lack of effectiveness in this study.…”
Section: Lvef Change Noted In Individual Studiesmentioning
confidence: 84%
“…In the study conducted by Wollert et al, 9 LV dysfunction was defined as hypokinesia or akinesia involving more than twothirds of the left ventricular anteroseptal, lateral, and/or inferior wall, as shown by angiography done immediately after PCI. In the trial by Lunde et al, 6 LV dysfunction was defined as 3 or more hypokinetic left ventricle segments observed on echocardiography. In the study by Schächinger et al, 5 LV dysfunction was defined as substantial residual left ventricular regional wall motion abnormality (as defined by an ejection fraction ≤45% according to a visual estimate).…”
Section: Data Synthesis and Analysismentioning
confidence: 99%
See 3 more Smart Citations